Radionuclide Diagnosis of Esophageal Dysmotility and Gastroesophageal Reflux in Patients with Systemic Sclerosis - R. A. Bashirov; L. E. Samoilenko; S. A. Ryzhkin; K. F. Vartanyan; D. A. Gimaletdinova; A. F. Yusupova; D. I. Abdulganieva; L. F. Ziganshina; E. S. Zamanova; E. V. Puzakin; A. A. Malov; B. M. Sharafutdinov (Вестник рентгенологии и радиологии)
Objective: to evaluate the possibilities of dynamic scintigraphy for the diagnosis of esophageal dysmotility (ED) and gastroesophageal reflux (GER) in patients with systemic sclerosis (SS).Material and methods. The study group included 77 patients with established SS of different disease duration (from several months to 30 years) who underwent Technephyt 99mTc dynamic esophageal scintigraphy using two-stage protocol. During the first stage, the esophageal transport function was evaluated; during the second stage, the presence and severity of GER were assessed. Scans were analyzed using visual assessment, quantitative estimation of time/activity curves, and a proposed three-point scale for evaluating ED and GER severity. The control group consisted of 19 practically healthy individuals who underwent a routine examination to exclude digestive system and gastrointestinal tract diseases, the algorithm of which included dynamic scintigraphy.Results. ED was found in 74 of 77 patients (96%). According to three-point scale, severe ED (3 points) was registrated in 41 (55%) patients, moderate ED (2 points) in 15 (21%), and mild ED in 18 (24%). GER was diagnosed in 35 of 77 cases (45%): mild GER in 13 (37%), moderate GER (2 points) in 22 (63%), and none of the patients was found to have severe GER (3 points). A significant relationship between the presence of GER and the severity of ED was not obtained, but a direct correlation was established between ED and GER severity.Conclusion. Most SS patients demonstrated ED of varying severity associated with mild and moderate GER in nearly 45% of the cases. The study results confirm the practical significance of dynamic scintigraphy for assessing the esophageal transport function and GER in SS patients.